Tinjauan Peraturan Baznas No.3 Tahun 2018 terhadap Penyaluran Bantuan Produktif di Baznas Kabupaten Purwakarta - Maharani Salma Fitriyah; Iwan Permana (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. In the productive aid distribution program in Baznas regulation No.3 of 2018 which managed by the National Amil Zakat Agency Of Purwakarta Regency, it can be efficient and effective in an effort to help Umkm in the National Amil Zakat Agency Of Purwakarta Regency. With this productive aid distribution program, it can change the standard of living of the mustahiq of the the National Amil Zakat Agency Of Purwakarta Regency because this assistance is allocated to Umkm of the National Amil Zakat Agency Of Purwakarta Regency. However, the fact on the ground is that the distribution of productive assistance has been distributed buth there is no further evaluation from the baznas on the mustahiq who have received the productive assistance which resulted in the aid not being allocated to develop umkm. The purpose of this study is to clearly know the Baznas Regulation No.3 of 2018 on Umkm activities as well as to find out the impact of the Baznas Regulation No.3 to Umkm. The research method is qualitative and data collection uses field research. The data source is using primary data and secondary data. The data collection technique is by means of observation and interviews. The result of this study is that the distribution of productive assistance has been running properly but there is a lack of more evaluation from baznas which has resulted in this Umkm assistance not achieving target. Abstrak. Dalam program penyaluran bantuan produktif dalam peraturan Baznas No.3 Tahun 2018 yang dikelola oleh Badan Amil Zakat Nasional Kabupaten Purwakarta dapat berdaya guna dan tepat guna dalam upaya membantu para umkm di Badan Amil Zakat Nasional Kabupaten Purwakarta. Dengan adanya program penyaluran bantuan produktif ini dapat merubah taraf kehidupan para mustahiq Badan Amil Zakat Nasional Kabupaten Purwakarta karena bantuan ini dialokasikan untuk para UMKM Badan Amil Zakat Nasional Kabupaten Purwakarta. Namun, fakta di lapangan terdapat penyaluran bantuan produktif telah tersalurkan tetapi tidak adanya evaluasi lebih dari pihak BAZNAS terhadap para mustahiq yang telah menerima bantuan produktif tersebut yang mengakibatkan bantuan tidak di alokasikan untuk mengembangkan UMKM. Tujuan penelitian ini mengetahui secara jelas peraturan baznas no.3 tahun 2018 terhadap kegiatan UMKM juga untuk mengetahui dampak dari peraturan baznas no.3 tahun 2018 tentang penyaluran bantuan produktif untuk UMKM. Metode penelitian adalah kualitatif dan pengumpulan data menggunakan field research. Sumber data yaitu menggunakan data primer dan data sekunder. Teknik pegumpulan data yaitu dengan cara observasi dan wawancara. Hasil dari penelitian ini adalah penyaluran bantuan produktif ini sudah berjalan dengan semestinya tetapi kurang adanya evaluasi lebih dari baznas yang mengakibatkan bantuan umkm ini tidak mencapai target yang di harapkan.